Germination fitness differs between penoxsulam resistant and susceptible Echinochloa phyllopogon biotypes - Haitao Gao; Jie Li; Jiaxing Yu; Yucheng Gu; Hongchun Wang; Liyao Dong (Agriculture Communications, 2025)
Echinochloa phyllopogon, a malignant weed that mostly reproduces through self-pollination in the paddy fields of Northeast China, currently presents critical resistance concerns. Multiple herbicide-resistant individuals were identified within the same population, and seeds from each biotype were propagated for three generations. Three biotypes resistant to penoxsulam exhibited varying degrees of cross-resistance to other acetolactate synthase (ALS) inhibitors. Sequencing results indicated that F4 generation seeds were homozygous with stably inherited mutations. A derived cleaved amplified polymorphic sequences (dCAPS) method was consistent with the sequencing results and can quickly and accurately detect specific ALS mutations in E. phyllopogon. Seed germination experiments revealed that at 200 ​mM NaCl concentration, the tE50 values of RNTSR (non-target-site resistance) and R197 (target-site resistance carrying ​Pro-197-Thr mutation) biotypes were 11.37 and ​> ​14 days, respectively, with mean germination times of 10.32 and 8.66 days, both longer than that of the susceptible (S) biotype. Under osmotic potential and soil burial conditions, the RNTSR biotype exhibited lower germination and emergence rates than the S biotype. Overall, RNTSR and R197 biotypes displayed significant germination fitness costs under extreme environmental conditions (e.g., temperature, salt concentration, osmotic potential, and burial depth) compared with S biotypes. This study elucidates the relationship between specific herbicide target enzyme mutations and weed germination fitness, providing theoretical guidance for in-field management of resistant E. phyllopogon.